EDUKASI DAN PENERAPAN MEDIA DIGITAL DALAM PEMBUATAN DAN PENDOKUMENTASIAN SURAT DINAS BERBASIS ARTERI - Amril Amir; Afnita Afnita; Farel Olva Zuve; Gustina Erlianti (JURNAL KEPEMIMPINAN DAN PENGURUSAN SEKOLAH, 2022)
This activity aims to provide an understanding of the application of digital media in the manufacture and documentation of official letters carried out at SMPN Padang Pariaman Regency. Based on observations, it is known that the structure and language used in official letters are still not in accordance with the rules of the Indonesian language. In addition, it was also found that the preparation and storage of archives in schools was still inadequate. School archives or documents are arranged in a cabinet, so it takes a long time to find them and is not well maintained due to improper arrangement and storage. Therefore, an activity is needed to correct errors in writing official letters and documenting existing school archives. Based on this explanation, it is necessary to conduct training activities regarding the creation and documentation of digital-based official letters using the Arterial application at SMP Negeri Padang Pariaman Regency, West Sumatra.